Children’s Picture Book Series on Exploring Children’s Development of a Balanced Identity - Charaqua Vania Rawiadji; Liem Satya Limanta (Institute of Research and Community Outreach - Petra Christian University, 2021)
This paper elaborates the project of creating picture-book stories for two to five years old of Indonesian children, which highlight the issue of identity development in children. Erik Erikson’s eight stages of psychosocial development will be the theoretical framework of this paper. In the first and second story, the main characters pass through the crisis of autonomy versus shame and doubt. They have strict and overprotective parents that caused them to doubt themselves. However, by believing in themselves and taking an action, they passed the crisis and developed a balanced identity. In the third, fourth, and fifth story, the main characters pass through the crisis of initiative versus guilt. They learn to be honest, to forgive, and to let go. Each action has its own risk, but by taking the initiative to do the right thing, they passed the crisis successfully and formed a balanced identity.Keywords: children picture-books, children development, psychosocial development, autonomy vs shame and doubt, initiative vs guilt, balanced identity